Teacher resilience in the face of uncertainty: experiences of Turkish teachers during the COVID-19 outbreak - Bavli, Bunyamin; Kortel, Ozge (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
The study aims to shed light on how Turkish teachers perceive 'teacher resilience' in the shadow of the COVID-19 Outbreak by exploring their experiences. Phenomenological design was adopted in the study and maximum variation sampling was employed in selection of participants who consisted of 15 teachers with different educational backgrounds. Data were obtained through semi-structured in-depth and focus group interviews and a qualitative content analysis method was executed in data analysis. The statements of the participant teachers were examined through four dimensions presented in the theoretical framework of Mansfield et al. (2012): Profession-Related, Social, Emotional and Motivational Dimensions. The findings revealed that Turkish teachers were not ready for online teaching and experienced certain challenges in the use of effective teaching methods, time management and learner engagement. The study uncovered low levels of emotional, but high levels of social resilience among teachers. They had challenges to manage their emotions, and cope with job demands and stress from time to time. However, they overcame these challenges by building supportive relationships, communicating with each other, seeking help and taking advice. Moreover, many of the teachers managed to stay motivated, persevere, and be positive in the face of the unprecedented challenges they experienced during the COVID-19 Pandemic.
Keywords: COVID-19 pandemic; distance education; online teaching; teacher resilience; teaching profession; Education & Educational Research